The Model of Political Da’wah Expression of NU Muslimat in East Java - Ishomuddin (International Journal of Asian Social Science, 2019)
In preaching Islam and political propaganda, there are various ways that are carried out by each group in the organization. Every Islamic organization such as Muhammadiyah, NahdlatulUlama (NU), etc., has a different style of da’wah. Muhammadiyah in its political mission used high political methods, not the party, while NU in its history through practical political channels. Although initially the methods carried out did not directly use political parties, which were packaged through recitations and routine activities, but in its development he established political parties. The same is true of the NU women’s organization, Muslimat NU. The mission of this organization is to build community and Muslim faith. But in practice he entered practical territory as a form of translation of his mission. From the aforementioned phenomena, the purpose of this research is to understand the expression model of political underwriting carried out by Muslimat NU. This research was conducted using a qualitative approach. Data collection uses observation, interviews, and documentaries. The data analysis was carried out using the Interactive analysis model of Miles, Huberman, Saldana.